2019
DOI: 10.1002/mp.13346
|View full text |Cite
|
Sign up to set email alerts
|

The VAMPIRE challenge: A multi‐institutional validation study of CT ventilation imaging

Abstract: Purpose CT ventilation imaging (CTVI) is being used to achieve functional avoidance lung cancer radiation therapy in three clinical trials (NCT02528942, NCT02308709, NCT02843568). To address the need for common CTVI validation tools, we have built the Ventilation And Medical Pulmonary Image Registration Evaluation (VAMPIRE) Dataset, and present the results of the first VAMPIRE Challenge to compare relative ventilation distributions between different CTVI algorithms and other established ventilation imaging mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 37 publications
2
89
0
Order By: Relevance
“…The level of smoothing that is applied to the ventilation images varies by research group and implementation. 19 …”
Section: Calculation Methodologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
“…The level of smoothing that is applied to the ventilation images varies by research group and implementation. 19 …”
Section: Calculation Methodologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
“…The voxel‐wise correlation coefficients ranged from 0.08 to 0.35 before correction, which are similar to those reported in the previous human studies comparing CT and ground truth ventilation images . Kipritidis et al observed median voxel‐wise correlations ranging from approximately 0 to 0.5 for 25 subjects with 68 Ga‐aerosol (Galligas) PET and 21 subjects with 99m Tc‐DTPA SPECT in a multi‐institutional study to evaluate 23 different methods of CT ventilation imaging (i.e., unique combinations of DIR and ventilation metric) …”
Section: Discussionmentioning
confidence: 99%
“…16 Tc-DTPA SPECT in a multi-institutional study to evaluate 23 different methods of CT ventilation imaging (i.e., unique combinations of DIR and ventilation metric). 23 The accuracy and precision of CT ventilation imaging may also be improved by strategies to reduce 4D-CT artifacts, such as improved sorting, [31][32][33][34][35] breathing guidance, 36,37 prospectively gated acquisition, [38][39][40] and image processing. 41,42 Combining the proposed correction method with such strategies may generate additional value for improving CT ventilation imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting affine transformation was then applied to the CT‐ventilation image and the voxel‐wise Spearman correlation was computed at the resolution of the SPECT ventilation, after applying a median filter with 3×3 structuring element to the SPECT image (as done in Ref. [20]).…”
Section: Methodsmentioning
confidence: 99%